Alf Ross”™ theory of legal validity in the context of current research on the judicial decision-making - ELIASZ, Katarzyna (Utopía y Praxis Latinoamericana, 2016)
The purpose of this article is twofold. Firstly, itÂ presents basic assumptions of Alf Ross”™ theory of legalÂ validity. Secondly, it examines validity of Ross”™ theory inÂ context of current psychological research into the judicialÂ decision-making. For Ross the utterance concerning validÂ legal rule is a prediction to the effect that the judge willÂ use the rule as the basis for his future decisions. SuchÂ predictions are possible on the assumption of objectiveÂ criterion motivating the judge”™s actions, which for Ross isÂ a normative ideology shared by the judges. Such ideologyÂ is based on the sources of law in the proper hierarchy.Â Individual factors, which cannot form a basis for strongÂ predictions are deliberately excluded from Ross”™ theory.Â Although he was fully aware of the complexity of humanÂ decision-making process, yet had to ignore that aspect ofÂ human motivation, which would be useless as a basis forÂ predictions. The question is whether a theory based on fullyÂ objective factors is in accordance with current research inÂ the field of judicial decision-making. The article analysesÂ some of the current researches in order to establish whetherÂ they give a clear image of the process of judging, and howÂ this image might affect Ross”™ theory of validity. As it is statedÂ no such clear image emerges from the current empiricalÂ data. For this reason, the allegation that Ross”™ theory isÂ empirically outdated cannot be sustained. Moreover, evenÂ if empirical data indicate that subjective criteria play aÂ significant part in judge”™s decisions, they will not undermineÂ Ross”™ predictive theory of legal validity.